A Subtitling Analysis Of Conjunction In Prince Of Persia: The Sands Of Time Movie - Wibowo, Dedy Cahyo, Dra. Dwi Haryanti, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
The objectives of the study are to describe the types of conjunction and their use in subtitling of Prince of Persia: The Sands of Time movie and to clarify the equivalence of conjunction in subtitling of Prince of Persia: The Sands of Time movie. This research is a descriptive qualitative research. The data of this research are sentences containing conjunction. The data source is subtitling of Prince of Persia: The Sands of Time movie. The writer uses documentation technique in collecting the data. The data are analyzed by using comparing method. The results of the research show that first, the writer finds that there are two types of conjunction in subtitling of Prince of Persia: The Sands of Time movie, namely coordinate conjunction and subordinate conjunction. From 189 data, there are 110 data or 58,2% of coordinate conjunction and 79 data or 41,8% of subordinate conjunction. The coordinate conjunction consists of 69 or 36,5% conjunctions that are used as cumulative, 5 or 2,64% conjunctions that are used as alternative, 28 or 14,81% conjunctions that are used as adversative, 8 or 4,23% conjunctions that are used as illative, and the subordinate conjunction consists of 13 or 6,87% conjunctions that are used as apposition, 5 or 2,64% conjunctions that are used as causation, 2 or 1,05% conjunctions that are used as purpose, 18 or 9,52% conjunctions that are used as condition, 9 or 4,76% conjunctions that are used as comparison, 9 or 4,76% conjunctions that are used as extent or manner, and 23 or 12,16% conjunctions that are used as time. The second, the writer finds that from 189 data, there are 183 data or 96,82% equivalent subtitling and 6 data or 3,18% non equivalent subtitling. Based on the data above, the translation of subtitling Prince of Persia: The Sands of Time movie is good.